Half Cauchy-Modified Exponential Distribution: Properties and Applications - Chaudhary, Arun Kumar; Kumar, Vijay (Nepal Journal of Mathematical Sciences, 2022)
A new distribution having three parameters using half Cauchy family of distribution named half Cauchy modified exponential distribution is deliberated and studied in this work. Its mathematical and statistical properties are examined. Model parameters of novel distribution are evaluated using least-square, maximum likelihood and Cramer-Von-Mises estimations approaches. R programming software is applied to carry out all of the calculations. To evaluate the new distribution's application and goodness-of-fit test, an actual data set is studied for illustration. The suggested new distribution is performed better as compared to some existing distributions.